2014
DOI: 10.1371/journal.pone.0092261
|View full text |Cite
|
Sign up to set email alerts
|

Seed Germination Ecology of Echinochloa glabrescens and Its Implication for Management in Rice (Oryza sativa L.)

Abstract: Echinochloa glabrescens is a C4 grass weed that is very competitive with rice when left uncontrolled. The competitive ability of weeds is intensified in direct-seeded rice production systems. A better understanding is needed of factors affecting weed seed germination, which can be used as a component of integrated weed management in direct-seeded rice. This study was conducted to determine the effects of temperature, light, salt and osmotic stress, burial depth, crop residue, time and depth of flooding, and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 30 publications
5
40
0
1
Order By: Relevance
“…These germination values were similar to those recorded in previous studies on E. glabrescens Munro ex Hook in which at a salt concentration of 200 mM the germination was more than 60% and averaged about 73% at 250 mM NaCl (Opeña et al, 2014); similar germination level (68%) was also found on E. crus-galli at a salt concentration of 225 mM (Sadeghloo et al, 2013). Conversely, in trials carried out by Chauhan and Johnson (2009), germination of E. colona (L.) Link was totally inhibited at the salt concentration of 200 mM.…”
Section: Germination Capacitysupporting
confidence: 91%
See 2 more Smart Citations
“…These germination values were similar to those recorded in previous studies on E. glabrescens Munro ex Hook in which at a salt concentration of 200 mM the germination was more than 60% and averaged about 73% at 250 mM NaCl (Opeña et al, 2014); similar germination level (68%) was also found on E. crus-galli at a salt concentration of 225 mM (Sadeghloo et al, 2013). Conversely, in trials carried out by Chauhan and Johnson (2009), germination of E. colona (L.) Link was totally inhibited at the salt concentration of 200 mM.…”
Section: Germination Capacitysupporting
confidence: 91%
“…At the same NaCl concentration Sadeghloo et al (2013) found that germination was completely inhibited. Previous studies on E. colona and E. glabrescens also found a linear decrease of germination with the increase of salt concentration (Chauhan and Johnson, 2009;Opeña et al, 2014). The EC50 for germination capacity was the lowest for the resistant population r2 (EC50 274.47 mM), while the highest for the sensitive population s3 (EC50 380.73 mM) ( Table 2).…”
Section: Germination Capacitymentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies found that some weed species, such as texasweed [Caperonia palustris (L.) St. (Opeña et al 2014) was significantly higher in light/dark conditions than in dark conditions. In our study, seeds could germinate in the dark, which indicates that light is not a prerequisite for germination of triquetrous murdannia.…”
Section: Resultsmentioning
confidence: 99%
“…Sementes de muitas espécies de plantas daninhas podem germinar apenas na presença de luz, enquanto outras germinam igualmente em condições de presença e ausência de luz (Opeña et al, 2014). Alguns estudos já constataram comportamento similar com espécies de Echinochloa colona, E. crusgalli e E. glabrescens, o que corrobora os resultados encontrados no presente estudo (Boyd & Acker, 2004;Chauhan & Johnson, 2011;Opeña et al, 2014).…”
Section: Resultsunclassified